Quantification and Stability Indicating UPLC Method Development and Validation of Acalabrutinib in Bulk and Pharmaceutical Dosage Form: Pharmaceutical Science-Pharmaceutical Analysis - Goud V, Mohan; Singh N, Pooja (International Journal of Life Science and Pharma Research, 2021)
Acalabrutinib (ABN) is a Bruton tyrosine kinase inhibitor used to treat mantle cell lymphoma, chronic lymphocytic leukemia and small lymphocytic lymphoma. It has been used in the treatment of Hodgkin lymphoma, multiple myeloma and ovarian cancer. It is available in capsule dosage form, usually prescribed twice a day. The objective of the present study describes the ultra-performance liquid chromatography (UPLC) method development and validation for the estimation of the ABN in Capsule dosage form by following ICH guidelines because no methods were reported in this category. The column and Mobile phase were selected based on trial and error methods. For the estimation, the chromatogram BEH C18 (50 mm x 2.1 mm, 1.7µm) column was run through with Mobile phase 0.01N KH2PO4 : Methanol in the ratio of 50:50 at a flow rate of 0.3 ml/min. Temperature was maintained at 30°C. Optimized wavelength selected for the separation was 234nm. Retention time was achieved 1.148minute in optimized chromatogram. Theoretical plate count and tailing factor were obtained “as per recommendations of ICH limits”. The % RSD precision obtained was 0.7% and Intermediate precision obtained was 0.7% as the limit of Precision was less than 2. %Recovery obtained for marketed formulation was 99.23%. LOD, LOQ values obtained from the regression equation (y=9128.5x + 14854) of ABN were 0.18µg/ml and 0.55µg/ml respectively. Proposed method was linear over the concentration range25-150µg/ml. Different degradation studies (acid, alkali, oxidation, thermal, UV, water) were performed and all these samples passed the limits of degradation. Retention time and run time was decreased, so the method developed was simple and economical that can be adopted in regular quality control tests in Industries.